#TITLE_ALTERNATIVE# - FLOBERT GULTOM (NIM:15112099), IVAN
ALOS-2 / PALSAR-2 is a SAR satellite that can be used for deformation observation. The emitted L-band wave is able to penetrate clouds and vegetation well through the topography, so it is used appropriately for deformation observation by InSAR method. One of the data acquisition technology of ALOS-2 / PALSAR-2 is ScanSAR which gives the possibility of deformation observation in a very wide area (study area is Central Java and surrounding). Observation of deformation in the Central Java and surrounding needs to be done, given the deformation of several North Coast of Central Java. Pekalongan has 7 - 10 cm deformation per year, and Semarang 7 - 13 cm per year [Chaussard et al., 2012].This study uses data from March 30th, 2015 to November 21st, 2016 with 12 observations. Based on the results in this study, there are seven areas that have deformation. In that seven areas, only Gunung Kidul shows deformation with a positive value in Line of Sight (LOS). The number of deformation rate in the region is 111 mm / year. The other six areas such as Cilacap has deformation rate -70 mm/year, Pekalongan has -74 mm/year, Semarang has -120 mm / year, Demak has -131 mm/year, Purwodadi - Blora has -124 mm/Year, and Lasem has -83 mm/year in LOS.